(untitled) - Rivers, Wilga M. (Cambridge, 2000)
In this collection of essays, a distinguished group of innovative teachers and writers describe the approaches and techniques they have incorporated into their own teaching. The articles are designed to help classroom teachers make language classes more participatory and communication oriented. Successive articles deal with the structure of interaction in large and small groups: imaginative activities for listening, speaking, reading, writing, and testing; the use of poetry, song, and drama; how to perform grammar rules rather than recite them; the special contribution of authentic materials; using audio and video as well as computer software to enhance learning, tapping the community as a resource; learning to interact in different cultural styles; and preparing the student for real-life professional use of language. Teachers of any language and teachers in training will find in this volume a wealth of original and practical ideas for the classroom.
Keywords: Language and languages; Study and teaching